PEMIKIRAN POLITIK DALAM TAFSIR FATH AL-QADIR: PEMBACAAN ATAS KONSEP KETATANEGARAAN DALAM AL-QURAN YANG DITULIS AL-SHAWKANY - Hanafi, Yusuf (Jurnal Ilmiah Ilmu Ushuluddin, 2012)
This paper discusses about the political thought in tafsir al qadir written by al-Shawkany.It is written in the paper that in the locus of political life of the state, there is aphenomenon that muslims fell the awkwardness in solving some fundamental problems,such as how to find the right relationship between Islam and politics, how toposition of Islamic law in the context of a modern democratic state, and how Islamiclaw should be understood and practiced. The awkwardness was later implicated in thebirth of various types of political experimentation. Islamic tradition of thought inpolitical philosophy did not develop because of political thought are taught in two differentdisciplines, namely discipline of Jurisprudence and discipline of philosophy. Ironically,in the tradition of Islamic scholarship that dominates is the discipline of jurisprudence,therefore we can not get out of the paradigm of political theology (politicaltheology).